Nanoparticle-Facilitated Therapy: Advancing Tools in Peripheral Nerve Regeneration - Shi S; Ou X; Cheng D (International Journal of Nanomedicine, 2024)
Shaoyan Shi, Xuehai Ou, Deliang Cheng Department of Hand Surgery, Honghui Hospital, Xi’an Jiaotong University, Xi’an Honghui Hospital North District, Xi’an, Shaanxi, 710000, People’s Republic of ChinaCorrespondence: Deliang Cheng, Department of Hand Surgery, Honghui Hospital, Xi’an Jiaotong University, Xi’an Honghui Hospital North District, Xi’an, Shaanxi, 710000, People’s Republic of China, Tel +86 18740308729, Email chengdeliang2003@163.comAbstract: Peripheral nerve injuries, arising from a diverse range of etiologies such as trauma and underlying medical conditions, pose substantial challenges in both clinical management and subsequent restoration of functional capacity. Addressing these challenges, nanoparticles have emerged as a promising therapeutic modality poised to augment the process of peripheral nerve regeneration. However, a comprehensive elucidation of the complicated mechanistic foundations responsible for the favorable effects of nanoparticle-based therapy on nerve regeneration remains imperative. This review aims to scrutinize the potential of nanoparticles as innovative therapeutic carriers for promoting peripheral nerve repair. This review encompasses an in-depth exploration of the classifications and synthesis methodologies associated with nanoparticles. Additionally, we discuss and summarize the multifaceted roles that nanoparticles play, including neuroprotection, facilitation of axonal growth, and efficient drug delivery mechanisms. Furthermore, we present essential considerations and highlight the potential synergies of integrating nanoparticles with emerging technologies. Through this comprehensive review, we highlight the indispensable role of nanoparticles in propelling advancements in peripheral nerve regeneration.Keywords: nanoparticle, nanomedicine, biomaterials, nerve regeneration, tissue